(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The question of literary types and genres is one of the most urgent problems of literary criticism. The specific features of a particular type or genre are revealed only in its historical, comparative and typological study with the literature of other peoples. Therefore, the features of the elegy genre live in Turkish, Arabic and Uzbek poetry as a special genre in a group of poems expressing sadness or unhappiness in Western countries, especially in English and French literature